Progress in Physical activity and Exercise and Affective and Anxiety Disorders: Translational Studies, Perspectives and Future Directions - Felipe Barreto Schuch (Frontiers Research Topics, 2015)
Physical activity and exercise were receiving a great attention as a strategy of prevention and treatment of affective and some anxiety disorders. Many studies have showed the efficacy of exercise in major depression and at depressed episode of bipolar patients, as well as, some authors shows the benefits of exercise in some anxiety disorders like Generalized Anxiety Disorder and Panic. Despite their efficacy, little is known concerning the main mechanisms related to the antidepressant and anxiolytic effects of exercise. Several studies in an animal model using Neurotrophic Factors, Oxidative Stress, Immunologic response and other biological markers reveal promising results. However, few studies were conducted in clinical samples. Additional to the antidepressant and anxiolytic effects, exercise appears improve QoL in major depressed, bipolar and anxiety patients. Theoretically, this increase may be associated with cognitive improvements, improvements at sleep quality, physical functioning, as well as other psychological issues as self-esteem, self-concept, and general well-being. The propose of this topic is to address the novelty and most recent research, related to antidepressant and anxiolytic effects of physical activity and exercise in patients with affective and anxiety disorders, as well as the issues associated with QoL improvement.The topic is looking for: - Clinical trials using exercise and physical activity as a treatment affective and anxiety disorders. - Studies investigating the optimal prescription factors (dose, volume, intensity, setting, frequency) associated with antidepressant and anxiolytic effects of physical activity and exercise for affective and anxiety disorder patients. - Original studies, comprehensive reviews, hypothesis and opinions concerning the mechanisms of antidepressant and anxiolytic effects of physical activity and exercise in affective and anxiety disorder patients. - Original studies, comprehensive reviews, hypothesis and opinions concerning other benefits of physical activity and exercise like : cognition, weight gain prevention and QoL in affective and anxiety disorder patients. - Translational research. - Studies of cost-efficacy analysis